2019
DOI: 10.1109/tsp.2019.2952052
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Sparse Array Beamforming Design for General Rank Signal Models

Abstract: The paper considers sparse array design for receive beamforming achieving maximum signal-to-interference plus noise ratio (MaxSINR) for both single point source and multiple point sources, operating in an interference active environment. Unlike existing sparse design methods which either deal with structured environment-independent or non-structured environment-dependent arrays, our method is a hybrid approach and seeks a full augumentable array that optimizes beamformer performance. This approach proves impor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…approach because both incorporate the apriori knowledge of interference parameters. Therefore, in comparing the data dependent designs, it is found that SDR design (also the SDR-symmetric [20]) is comparable to the DNN-EN design, with the DNN-SBSA is marginally suboptimal with the average performance degradation of 0.37 dB. This slight performance trade off is readily leveraged by the real time realization of the DNN-SBSA algorithm implementing the Capon beamformer in time frames of the order of few milli-seconds.…”
Section: Performance Comparisions With State-of-the-artmentioning
confidence: 95%
See 3 more Smart Citations
“…approach because both incorporate the apriori knowledge of interference parameters. Therefore, in comparing the data dependent designs, it is found that SDR design (also the SDR-symmetric [20]) is comparable to the DNN-EN design, with the DNN-SBSA is marginally suboptimal with the average performance degradation of 0.37 dB. This slight performance trade off is readily leveraged by the real time realization of the DNN-SBSA algorithm implementing the Capon beamformer in time frames of the order of few milli-seconds.…”
Section: Performance Comparisions With State-of-the-artmentioning
confidence: 95%
“…The performance of the proposed SBSA, DNN-EN and DNN-SBSA are compared with existing work on sparse array design which is based on SDR and SCA approaches [19], [20]. It is clear from Fig.…”
Section: Performance Comparisions With State-of-the-artmentioning
confidence: 99%
See 2 more Smart Citations
“…From the perspective of array structure, these methods can be divided into two major categories. The first class is the sparse selection approach [1][2][3][4][5][6], which is based on arrays that are uniformly arranged (usually array elements spaced half a wavelength apart), and a portion of the array elements are selected to be unexcited based on the optimization results. The second class is the sparse array design method [7][8][9][10][11][12][13][14][15][16][17][18][19][20], in which the array elements are randomly arranged on the array plane.…”
Section: Introductionmentioning
confidence: 99%